Can agroforestry provide a future for cocoa? Implications for policy and practice - Olwig, M.F.; Asare, R.; Vaast, P.; Bosselmann, A.S. (Palgrave Macmillan, 2024)
Climate change is threatening cocoa production in Ghana, the world’s second largest cocoa exporter. Yet, as we have shown in this book, the impacts of climate change must be understood in the context of the multiple socioeconomic and biophysical pressures facing cocoa farmers, including the conversion of farms for other land uses, increasing hired labor costs as well as pests and diseases. This final chapter summarizes the book’s overall findings on cocoa agroforestry as climate change adap-tion and points to ways forward in terms of policy, practice and research. Our findings suggest that a nuanced view of farmers, agroecosystems and sites is necessary and emphasize the need to study shade tree species and species diversity, in addition to shade levels, to optimize the sustain-ability of cocoa farming. We further suggest that it may not be possible to sustainably grow cocoa in marginal regions of the cocoa belt, where yields are lower and where agroforestry may be unable to mitigate the negative impacts of the adverse climate. Finally, we point to the impor-tance of considering rights and access to trees, land, extension services and resources, and call for more multidisciplinary research on differently situated farmers’ opportunities and needs.